Analysis of the Relationship of Maternal Age and Parity to Gestational Diabetes Risk (Oshada, 2025)
This study aims to analyze the association between maternal age and parity with the risk of gestational diabetes mellitus (GDM) using a quantitative analytic observational approach. Data were collected from scientific literature, epidemiological reports, and global health policy documents published between 2018 and 2025, focusing on the Southeast Asian region. The findings reveal that maternal age above 30 years is significantly correlated with higher GDM prevalence, with the risk sharply increasing among women aged ≥35 years. High parity (≥3 births) contributes to cumulative metabolic burden, greater insulin resistance, and elevated GDM likelihood. The interaction between maternal age and parity demonstrates a synergistic effect, reinforced by biological and social factors, including limited antenatal access and low nutritional awareness. From a public health perspective, these findings highlight the need for integrated maternal risk-based screening, preconception education, and digital health interventions to identify high-risk women early. Community-based preventive strategies and the use of digital health technologies can enhance GDM prevention, strengthen maternal and child health outcomes, and contribute to sustainable health development goals across Southeast Asia.